Desimination of august 17 competition in Padukuhan Nangsri Kidul Kalurahan Candirejo - Iswanto Suwarno; Robbi Rahim; Mohammad Aljanabi; Omar Tanane; Erwin L. Rimban; Manvender Kaur Sarjit Singh (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Early childhood education and children's education in kindergarten are efforts to form, develop character aimed at children from birth to the age of six. The teaching that is carried out in providing educational stimulation is carried out in a fun way, one of which is in carrying out learning that is packed with competitions. Since the Covid-19 pandemic, the residents of Nangsri Kidul have never held the 17 August competition again. Therefore the KKN team took the initiative to make the August 17 competition one of our work programs so that the people in Padukuhan Nangsri Kidul can celebrate and enliven the Republic of Indonesia's second anniversary through the August 17 competition. To make the August 17 competition a success, we are working with the Padukuhan Youth Organization Nangsri Kidul to prepare for this competition. The competition was held for two days, namely on 6 and 7 August 2022. This competition took place at the Padukuhan Nangsri Kidul volleyball court. Several competitions were held, such as eating crackers, water relay, sack race, marble relay, and fashion shows.